Course and treatment of chronic hepatitis E virus infection in lung transplant recipients. Issue 2 (20th January 2014) - Pischke, S.; Greer, M.; Hardtke, S.; Bremer, B.; Gisa, A.; Lehmann, P.; Haverich, A.; Welte, T.; Manns, M.P.; Wedemeyer, H.; Gottlieb, J.; ,
Abstract Objective Persistent hepatitis E virus (HEV) infections have been described in various transplant cohorts. However, the frequency and the course of HEV infection in lung transplant recipients (Lu‐Tr) are not well defined. Methods We retrospectively analyzed serum from 95 Lu‐Tr for HEV RNA and anti‐HEV immunoglobulin‐G (IgG) (with the MP assay). Anti‐HEV seroprevalence was compared to that of 537 healthy individuals. Prospective HEV screening was subsequently initiated in Lu‐Tr. Results Elevated liver enzymes were observed in 44/95 (46.3%) patients. Anti‐HEV IgG was present in 5/95 patients (5.3%), revealing a slightly higher prevalence compared to controls (2%, 11/537; P = 0.07). Chronic HEV infection with detectable viral replication was confirmed by polymerase chain reaction in 3 (3.2%) patients, all of whom demonstrated clinical and biochemical features of active liver disease (maximum alanine aminotransferase [ALTmax] 89, 215, and 270 IU/L, respectively). One patient had died from multi‐organ failure in combination with liver cirrhosis before HEV diagnosis. Two additional patients with chronic hepatitis E were identified during prospective screening (ALTmax 359 and 318 IU/L). All patients still alive commenced ribavirin therapy for 5 months, with dose adjustment (400–600 mg/day) according to renal function and hemoglobin level. Sustained resolution of HEV infection occurred in 2 patients. One patient is still under treatment, and the fourth died from graft failure considered unrelated to ribavirin therapy. Conclusion Chronic hepatitis E should be considered in the differential diagnosis of elevated liver enzymes, which are commonly seen in Lu‐Tr. We observed 1 case of end‐stage liver cirrhosis and death in an HEV‐infected subject, who was not treated with ribavirin. Given this potentially devastating consequence, ribavirin therapy of persistent HEV infection appears to be acceptably safe and effective in Lu‐Tr. However, larger prospective studies are warranted.